Forecasting Demand for Electric Batik Stoves Using Moving Average Method in CV. A B C - Gunawan Budi Susilo (Journal of Industrial Engineering and Halal Industries, 2022)
Today's economic problems cause companies to be able to manage finances. For companies engaged in production, it is essential to manage finances so that the company does not experience losses. To overcome this, companies need to make optimal production and demand planning. Demand planning, in general, is better known as forecasting. The single-moving average method uses actual demand data to generate forecast values for future demand. This method will be effectively applied if the product's market demand remains stable. This method has two unique properties: making a forecast requires historical data within a certain period, and the longer the moving average, the smoother the moving average will be. The results showed three samples of stoves, namely, type A-AS001 with a MAD value of 118.16, an MSE value of 44015.27, and a MAPE value of 3.93. The type A-AS002 stove shows a MAD value of 7.81, an MSE value of 92.23, and a MAPE value of 0.27. The type A-SD001 stove has a MAD value of 16.16, an MSE value of 550.75, and a MAPE value of 3.72.